2016
DOI: 10.1021/acs.organomet.6b00771
|View full text |Cite
|
Sign up to set email alerts
|

Stable Mono- and Dinuclear Organosilver Complexes

Abstract: A series of mononuclear and dinuclear complexes of silver(I), supported by an N-heterocyclic carbene and bound to sp 3 -, sp 2 -, and sp-hybridized carbanions, has been synthesized. Synthetic routes include transmetalation from organozinc, organomagnesium, and organosilicon reagents, as well as the deprotonation of a terminal alkyne. These complexes exhibit greater thermal stability than typical organosilver reagents, permitting spectroscopic and structural characterization. The carbanion-bridged disilver cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 148 publications
1
23
0
Order By: Relevance
“…As econd structure with ethyl ligands bridging Cr centers,[ ((t-Bu)NP-(Ph) 2 N(t-Bu))Cr(m-Et)] 2 , [9] however shows amoderate degree of asymmetry in the methylene carbon atoms with respect to the metal centers,w hile the methyl carbon atoms are highly asymmetric to the extent that one Cr···C(methyl) distance for each metal is only approximately 0.5 greater than the sum of the covalent radii of the individual atoms. [10] Thefinal two reports show acation, {[(SIPr)Ag] 2 (m-Et)} + ,that has ahighly symmetric ethyl bridge [11] and an anion, {[Et 2 Zn] 2 (m-Et)} À , whose disordered metal centers prevented detailed discussion of bond lengths and angles. [12] Fors imple ferric salt cross-couplings with alkyl Grignard reagents,t he addition of NMP as ac o-solvent leads to significantly improved cross-coupling yields with b-hydrogencontaining alkyl Grignard reagents.…”
mentioning
confidence: 99%
“…As econd structure with ethyl ligands bridging Cr centers,[ ((t-Bu)NP-(Ph) 2 N(t-Bu))Cr(m-Et)] 2 , [9] however shows amoderate degree of asymmetry in the methylene carbon atoms with respect to the metal centers,w hile the methyl carbon atoms are highly asymmetric to the extent that one Cr···C(methyl) distance for each metal is only approximately 0.5 greater than the sum of the covalent radii of the individual atoms. [10] Thefinal two reports show acation, {[(SIPr)Ag] 2 (m-Et)} + ,that has ahighly symmetric ethyl bridge [11] and an anion, {[Et 2 Zn] 2 (m-Et)} À , whose disordered metal centers prevented detailed discussion of bond lengths and angles. [12] Fors imple ferric salt cross-couplings with alkyl Grignard reagents,t he addition of NMP as ac o-solvent leads to significantly improved cross-coupling yields with b-hydrogencontaining alkyl Grignard reagents.…”
mentioning
confidence: 99%
“…Before exploring the CF 3 group transfer from Ag to (dppp)Pd(Ph)I, we establisheda satouchstone the trifluorome-thylationof1 with the widelyu sed nucleophilic trifluoromethyl sourcesR 3 SiCF 3 (R=Me, [9] Et [4b,h,i] )i nc ombination with CsF.A fter 30 minutes, we only observed 2 in 19 %a nd traces using Me 3 SiCF 3 and Et 3 SiCF 3 ,r espectively (Figure 2a). [10] With these results as ar eference, we then focused on the activity of the scarce examples of isolated trifluoromethylsilver(I)c ompounds reportedi nt he literature to date:S IPrAgCF 3 [11] [SIPr = bis(1,3bis(2,6-diisopropylphenyl)imidazol-2-ylidene)] and (bathophenanthroline)Ag(CF 3 ). [12] The treatment of (dppp)Pd(Ph)I with 1.5 equiv of SIPrAgCF 3 (3) [13] resulted in < 5% yield of (dppp)Pd(Ph)(CF 3 )a fter 30 minutes (Figure 2a).…”
mentioning
confidence: 99%
“…Previous studies have proved that organosilver complexes have limited stability. 26 However, complexes 2a–2e are quite stable upon exposure to air and moisture. Preliminary reactivity studies revealed that reaction of 2a with CF 3 COOD gave rise to 2,3-deuterated indole in high yield, suggesting the nucleophilic nature of the Ag–C bonds.…”
Section: Resultsmentioning
confidence: 99%